Barriers to the Adoption of Sustainable Construction - Chigozie Osuizugbo, Innocent; Oyeyipo, Opeyemi; Lahanmi, Ayodele; Morakinyo, Adesoye; Olaniyi, Olusola (European Journal of Sustainable Development, 2020)
Studies have shown that adoption of sustainable construction practice would result in a substantial reduction in the greenhouse emissions from the construction industry. Evolving a sustainable development practice is an emergent concern for the construction industry in both developing and developed countries. Sustainable construction is concerned with site planning and design, community, indoor air quality, energy, materials, water, commissioning and marketability for the benefit of mankind. This requires enormous efforts from all the stakeholders in the industry. Sustainable construction efforts in the Nigerian construction industry have been ineffective as a result of a number of barriers that prevent a smooth transition to sustainable construction practice in the country. The aim of this study is to assess the potential barriers that hinder effective adoption of sustainable construction practice in the Nigerian Construction Industry, with a view to exploring how these barriers can be overcome and thereby achieving sustainable construction in the country. A cross-sectional questionnaire was adopted for the survey. Purposive sampling technique was used to elicit 105 copies of questionnaires from various construction professionals based in Lagos state, Nigeria. Data collected were analysed using frequency, percentage, mean, relative importance index and ranking. The results revealed that key barriers to sustainable construction in the Nigerian Construction Industry are poor government support for sustainable construction, lack of relevant laws and regulations to drive sustainable construction, lack of demand for sustainable construction from clients, low level of awareness of sustainable construction and fear of the cost of adopting sustainable construction. Based on the findings from this study, it was recommended that government should assume a greater role in the popularisation and application of sustainable strategy. The barriers identified and the suggestions made to minimize barriers to the adoption of sustainable construction in Nigeria should offer an enabling environment for stakeholders in construction sector to smoothly adopt sustainable construction for the benefit of humanity.